Architectural modelmaking - Dunn, Nick. (London : Laurence King Publishers, 2010)
This book focuses on the inspiring possibilities for creating three-dimensional, physical models of the built environment with all the different media and techniques that are now available. Through description of the use of different models in different contexts, the book provides a practical and effective guide to how and why models are used, in addition to what they are used for, and how they relate to architecture education.
Keywords: Architectural models; Architectural models--Design and construction